Entrepreneurial characteristics and intentions among undergraduates in Malaysia. (4th November 2019) - Abdul, Mohani; Rahman, Azmawani Abd.; Yahya, Mastora; Rahman, Mohammad Mizanur
This study investigates the entrepreneurial intentions of undergraduate students in the public university and private institution of higher learning in Malaysia. Six entrepreneurial characteristics were observed during the focus group interviews which included; risk taking propensity, self-confidence, need for achievement, innovativeness, tolerance of ambiguity, and locus of control. These elements are used to define the entrepreneurial profile of students using the trait model of entrepreneurship as a basis of the proposed research. Ten students from the public and private higher institutions of learning were interviewed. Students were selected from one public university (IPTA) and another from private university (IPTS). Results based on the students' entrepreneurial intentions are compared between the IPTA and IPTS and some plausible explanations are discussed. This research provides deeper insight into entrepreneurship education besides providing comprehensive empirical evidence about the impact of higher education on entrepreneurial intentions, thus fills an important gap in the entrepreneurship literature.